In vivo localization of chronically implanted electrodes and optic fibers in mice - Bálint Király (Nature Portfolio, 2020)
Király et al. propose a method combining micro-CT and MRI imaging to precisely localize electrodes and optic fibers in the mouse brain in vivo. This allows assessing the success of targeting after surgery, depth adjustment of movable probes and identifying systematic errors in the surgical process.